Physical activity and academic achievement in children: A historial perspective - Howie, Erin; Pate, R. (Shanghai Tiyu Xueyuan, 2012)
As the focus on academic achievement has increased, physical activity (PA) opportunities in schools have decreased in the United States. In an attempt to discover how the decline in PA may affect academic achievement, researchers have been studying the effects of PA on cognition and academic achievement in children for more than 50 years. This review takes a historical perspective on the science of PA and academic achievement prior to and during the past 5 years. A total of 125 published articles were included and reviewed. Fifty-three of these articles were published in the past 5 years. In recent years, the overall quality of the studies has increased, but the results continue to be inconsistent. Many use cross-sectional designs and the methods vary substantially. The majority of conclusions show a positive effect of PA on constructs related to academic achievement. Future studies should use strong study designs to examine the types and doses of PA needed to produce improvements in academic achievement.